A kind of UV insulation protective glue for new energy battery and preparation method thereof
By using UV insulating protective glue compounded with polyurethane acrylate and fluorosilicone modified acrylate in new energy batteries, the problem of easy separation and puncture of new energy batteries in the prior art is solved, and better adhesion stability, insulation and impact resistance are achieved.
Patent Information
- Application Number
- CN202410318855.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-03-20
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-03-20
AI Technical Summary
When new energy batteries are subject to external impacts for a long time, existing UV insulating glue is prone to separation and puncture, reducing the safety of use.
The UV insulating protective glue prepared by combining polyurethane acrylate with fluorosilicone modified acrylate, and adding diluted monomer, insulating filler, dispersant, photoinitiator and antioxidant.
The insulating protective film is formed through photocuring, which improves the bonding stability and puncture resistance of new energy batteries, reduces separation and puncture conditions, and improves the safety of use.
Smart Images

Figure BDA0004749885490000051 
Figure BDA0004749885490000061 
Figure BDA0004749885490000071
Abstract
Description
Technical Field
[0001] The present application relates to the field of new energy battery protection materials, and more specifically, it relates to a UV insulating protective glue for new energy batteries and a preparation method thereof. Background Art
[0002] New energy batteries are made by connecting multiple cells in series and arranging them closely to form a battery pack, which can save space while improving battery life. Since the distance between adjacent cells is small, when arranging the cells, it is necessary to use insulating protective materials to insulate the cells so that the battery pack has better sealing insulation, reducing the battery pack from being easily leaked or burned due to long-term exposure to high temperatures during use, thereby causing safety issues.
[0003] The insulating protection material of new energy batteries is generally blue film, which is a single-sided tape made of PSA pressure-sensitive adhesive on the back of a PET substrate. However, the bonding stability of blue film to new energy batteries is low, which limits its application in new energy batteries.
[0004] At present, some people have proposed to use UV insulating glue to replace blue film for application in new energy batteries. UV insulating glue is generally made of polyurethane acrylate, insulating filler, diluent monomer, initiator and other additives. Compared with blue film, it has better adhesion, construction convenience and insulation. However, although the addition of insulating filler improves the insulation of UV insulating glue, when new energy batteries are subjected to external impact for a long time, the battery pack of new energy batteries is still prone to separation and puncture, which reduces the safety of new energy batteries. Therefore, the current UV insulating glue needs further improvement. Summary of the invention
[0005] In order to solve the problem that the current UV insulating glue, when used in new energy batteries, is prone to separation and puncture of the battery pack when subjected to external impact for a long time, the present application provides a UV insulating protective glue for new energy batteries and a preparation method thereof.
[0006] In the first aspect, the present application provides a UV insulating protective adhesive for new energy batteries, which adopts the following technical solution:
[0007] A UV insulating protective adhesive for new energy batteries is prepared from the following raw materials in parts by weight:
[0008] Polyurethane acrylate 40-60 parts
[0009] Fluorosilicone modified acrylate 10-20 parts
[0010] Dilute monomer 25-35 parts
[0011] Insulation filler 28-38 parts
[0012] Photoinitiator 5-12 parts
[0013] Dispersant 4-8 parts
[0014] 1-3 parts of antioxidants.
[0015] By adopting the above technical scheme, the present application uses polyurethane acrylate as a reactive resin and compounds it with fluorosilicon modified acrylate, wherein polyurethane acrylate has good adhesion and softness, but low wear resistance and temperature resistance; fluorosilicon modified acrylate has both fluorine-containing segments and silicon-containing segments, giving fluorosilicon modified acrylate better insulation, adhesion stability, impact resistance and flexibility. Therefore, polyurethane acrylate and fluorosilicon modified acrylate produce good synergistic effects, with the diluent monomer as an active diluent, and the insulating filler plays the role of insulation and reinforcement, and can be stably cross-linked under the action of the photoinitiator; the dispersant and fluorosilicon modified acrylate produce good synergistic effects, so that the insulating filler is stably dispersed in the acrylate cross-linking system, and the prepared UV insulating protective glue has good adhesion stability, insulation and impact resistance, and is used in new energy batteries, and light curing forms an insulating protective film, which is not easy to separate or puncture after long-term use.
[0016] Preferably, the fluorosilicone modified acrylate is prepared from the following raw materials in parts by weight:
[0017] Methyl methacrylate 15-25 parts
[0018] Polypropylene glycol diglycidyl ether 5-10 parts
[0019] 4-6 parts of 4-hydroxybutyl acrylate glycidyl ether
[0020] 3-8 parts of trifluoroethyl methacrylate
[0021] 4-8 parts of vinyl trisbutyl ketoxime silane
[0022] Catalyst 0.1-0.3 parts
[0023] Inhibitor 0.05-0.1 parts.
[0024] By adopting the above technical scheme, methyl methacrylate and 4-hydroxybutyl acrylate glycidyl ether are used as reaction monomers, trifluoroethyl methacrylate is used as a fluorine-containing monomer, and vinyl trisbutyl ketoxime silane is used as a silicon-containing monomer. A polymerization reaction is carried out under the uniform catalysis of a catalyst and an inhibitor, and a fluorine-containing segment and a silicon-containing segment are introduced into the acrylate system. Polypropylene glycol diglycidyl ether is used as a dispersing aid containing a long-chain soft ether group, which can improve the stretchability of the molecular segments of each component, so that each component can fully react, thereby improving the grafting rate of the prepared fluorosilicone modified acrylate. The fluorosilicone modified acrylate prepared in this way can not only improve the adhesion stability and flexibility of the prepared UV insulating protective adhesive, but also can play a good synergistic role with the dispersant, improve the dispersion stability of the insulating filler in the system, and thereby improve the insulation and impact resistance of the prepared UV insulating protective adhesive.
[0025] Preferably, the fluorosilicone modified acrylate is prepared by the following steps:
[0026] A1. Add methyl methacrylate, polypropylene glycol diglycidyl ether and 4-hydroxybutyl acrylate glycidyl ether into a reaction device, heat to 60-70° C., mix and stir for 20-40 minutes to obtain a mixture A;
[0027] A2. Add trifluoroethyl methacrylate, vinyl tributylidene silane, a catalyst and a polymerization inhibitor to the mixture A, introduce nitrogen protection, raise the temperature to 85-95° C., react for 2-5 hours, and obtain fluorosilicone modified acrylate.
[0028] By adopting the above technical scheme, the reaction monomer is firstly evenly dispersed in polypropylene glycol diglycidyl ether, and then reacted, so as to prepare fluorosilicone modified acrylate with stable performance and high grafting rate.
[0029] Preferably, the diluent monomer is composed of a hydroxy acrylate monomer and a glycidyl ether acrylate monomer in a weight ratio of (2-3.5):(0.5-1.5).
[0030] Preferably, the glycidyl ether acrylate monomer is glycidyl methacrylate and / or bisphenol A diglycidyl ether diacrylate.
[0031] Preferably, the hydroxy acrylate monomer is any one or a combination of trimethylolpropane triacrylate, pentaerythritol triacrylate, pentaerythritol diacrylate, and tripropylene glycol diacrylate.
[0032] By adopting the above technical solution, the UV insulating protective adhesive prepared by using the above diluted monomer has good flexibility and impact resistance.
[0033] Preferably, the dispersant is composed of castor oil-modified polyol and vinyl triethoxysilane in a weight ratio of 1:(0.3-0.6).
[0034] By adopting the above technical scheme, castor oil-modified polyol has good weather resistance and film-forming properties, and can produce good synergistic effects with vinyl triethoxysilane, so that the insulating filler is evenly dispersed in the system, thereby improving the insulation and impact resistance of the prepared UV insulating protective adhesive.
[0035] Preferably, the insulating filler is any one or a combination of silicon dioxide, silicon powder, aluminum nitride, zinc oxide, and white carbon black.
[0036] By adopting the above technical solution, the above insulating filler has good insulating and reinforcing effects, and can improve the insulation and impact resistance of the prepared UV insulating protective glue.
[0037] Preferably, the photoinitiator is any one or a combination of 2-hydroxy-2-methylpropiophenone, 1-hydroxycyclohexyl phenyl ketone, and ethyl 2,4,6-trimethylbenzoylphenylphosphonate.
[0038] By adopting the above technical solution, the above photoinitiator has a good cross-linking initiating effect, so that the system is uniformly cross-linked and cured to form an insulating protective film with good adhesion stability, insulation and impact resistance.
[0039] Preferably, the antioxidant is a combination of at least two of antioxidant 1010, antioxidant 1076, antioxidant 168, and antioxidant 626.
[0040] By adopting the above technical solution, the above antioxidant has good antioxidant performance and can improve the antioxidant performance of the prepared UV insulation protective adhesive.
[0041] In the second aspect, the present application provides a method for preparing a UV insulating protective adhesive for new energy batteries, using the following technical solution:
[0042] A method for preparing a UV insulating protective adhesive for a new energy battery comprises the following steps:
[0043] S1, adding polyurethane acrylate, fluorine silicon modified acrylate and diluent monomer into a reaction device, and performing vacuum stirring to obtain a mixture I;
[0044] S2. Add insulating filler, initiator, dispersant and antioxidant to mixture I, stir evenly in vacuum, and keep warm to obtain UV insulating protective adhesive.
[0045] By adopting the above technical solution, a UV insulating protective glue for new energy batteries with stable performance and uniform system dispersion is prepared.
[0046] Preferably, in the steps S1-S2, the vacuum degree of vacuum stirring is -0.8MPa--1.0MPa; the insulation time in the step S2 is 1-2h, and the insulation temperature is 35-45°C.
[0047] By adopting the above technical solution, the better vacuum degree can make the components mix evenly and improve the dispersion efficiency, and the better insulation conditions can further improve the system stability of the prepared UV insulation protective glue.
[0048] In summary, this application has the following beneficial effects:
[0049] 1. The UV insulating protective glue for new energy batteries of the present application is compounded with polyurethane acrylate and fluorosilicone modified acrylate, and is compounded with diluent monomers, insulating fillers, dispersants, photoinitiators and antioxidants. The prepared UV insulating protective glue has good adhesion stability, insulation and impact resistance. It is applied to new energy batteries and forms an insulating protective film through photocuring. It has good fitting stability for new energy batteries, is not easy to separate, and has good puncture resistance.
[0050] 2. By using methyl methacrylate and 4-hydroxybutyl acrylate glycidyl ether as reaction monomers, polypropylene glycol diglycidyl ether as a dispersing aid, trifluoroethyl methacrylate as a fluorine-containing monomer, and vinyl tributylidene oxime silane as a silicon-containing monomer, a polymerization reaction is carried out under the uniform catalysis of a catalyst and an inhibitor to prepare a fluorosilicone modified acrylate, which can improve the adhesion stability, insulation and impact resistance of the prepared UV insulating protective adhesive.
[0051] 3. By using castor oil-modified polyol and vinyl triethoxysilane as dispersants, a good synergistic effect can be produced with fluorosilicone-modified acrylate, thereby improving the dispersion stability of the insulating filler in the system and thereby improving the performance of the prepared UV insulating protective adhesive. DETAILED DESCRIPTION
[0052] The present application is further described in detail below with reference to the embodiments.
[0053] The following are the sources and specifications of some raw materials of this application. The raw materials used in the preparation examples and embodiments of this application can be obtained from the market, including but not limited to the raw materials of the following models and manufacturers. Raw materials with equivalent performance can be used:
[0054] 1. Polyurethane acrylate: Allnex, EBECRYL 270;
[0055] 2. Fluorosilicone modified acrylate: commercially available from Yibo Strontium (Guangzhou) Nanotechnology Co., Ltd., content 50%, viscosity 1200-1600 Pa·s.
[0056] 3. Polypropylene glycol diglycidyl ether: CAS No. 26142-30-3;
[0057] 4. 4-Hydroxybutyl acrylate glycidyl ether: CAS No.: 119692-59-0, 1.077 g / cm 3 ;
[0058] 5. Trifluoroethyl methacrylate: CAS No.: 352-87-4, content 99%;
[0059] 6. Vinyl trisbutyl ketoxime silane: CAS No.: 2224-33-1, specific gravity 0.99±0.005g / ml;
[0060] 7. Castor oil modified polyol: Chuangye Biotechnology, CY006, hydroxyl value 20-50gKOH / 100g;
[0061] 8. Silicon dioxide: particle size 100-200nm;
[0062] 9. Zinc oxide: Bajiao brand, superior quality, content greater than 99.7%;
[0063] 10. White carbon black: Cabot, CAB-O-SIL TS620.
[0064] Preparation Example of Fluorosilicone Modified Acrylate
[0065] Preparation Example 1
[0066] Preparation Example 1 discloses a fluorosilicone modified acrylate, which is prepared by the following steps:
[0067] A1. Add 1.5 kg of methyl methacrylate, 0.5 kg of polypropylene glycol diglycidyl ether and 0.4 kg of 4-hydroxybutyl acrylate glycidyl ether into a reaction kettle, heat to 60° C., mix and stir for 20 min to obtain a mixture A;
[0068] A2. Add 0.3 kg of trifluoroethyl methacrylate, 0.4 kg of vinyl tributylidene oxime silane, 0.01 kg of azobisisobutyronitrile as a catalyst and 0.005 kg of p-hydroxyanisole as an inhibitor into the mixture A, introduce nitrogen protection, heat to 85 ° C, react for 2 h, and obtain fluorosilicone modified acrylate.
[0069] Preparation Example 2-3
[0070] The difference between Preparation Example 2-3 and Preparation Example 1 is that the amount of raw materials used and the preparation conditions are different, see Table 1 below for details.
[0071] Table 1 Raw material dosage and preparation conditions of Preparation Example 2-3
[0072]
[0073]
[0074] Preparation Comparative Example 1
[0075] The difference between Preparation Comparative Example 1 and Preparation Example 1 is that an equal amount of 4-hydroxybutyl acrylate glycidyl ether is replaced by polypropylene glycol diglycidyl ether, and the rest is the same as Preparation Example 1.
[0076] Preparation Comparative Example 2
[0077] The difference between Preparation Comparative Example 2 and Preparation Example 1 is that an equal amount of polypropylene glycol diglycidyl ether is replaced by 4-hydroxybutyl acrylate glycidyl ether, and the rest is the same as Preparation Example 1.
[0078] Preparation Comparative Example 3
[0079] The difference between Preparation Comparative Example 3 and Preparation Example 1 is that an equal amount of 4-hydroxybutyl acrylate glycidyl ether is replaced by trimethylolpropane triacrylate, and the rest is the same as Preparation Example 1.
[0080] Preparation Comparative Example 4
[0081] The difference between Preparation Comparative Example 4 and Preparation Example 1 is that an equal amount of vinyltributylonoxime silane is replaced by vinyltriethoxysilane, and the rest is the same as Preparation Example 1.
[0082] Preparation Comparative Example 5
[0083] The preparation process in Comparative Example 5 is as follows: 0.3 kg of trifluoroethyl methacrylate, 0.4 kg of vinyl trisbutyl ketoxime silane, 2 kg of n-butyl acetate as a solvent, 0.01 kg of azobisisobutyronitrile as a catalyst and 0.005 kg of p-hydroxyanisole as an inhibitor were added to 1.5 kg of methyl methacrylate, nitrogen was introduced for protection, the temperature was raised to 85 ° C, and the reaction was carried out for 2 hours to obtain fluorosilicone modified acrylate.
[0084] Example
[0085] Example 1
[0086] Example 1 discloses a UV insulating protective glue for new energy batteries, which is prepared by the following steps:
[0087] S1, adding 4 kg of polyurethane acrylate, 1 kg of commercially available fluorosilicone modified acrylate and a diluent monomer consisting of 2 kg of trimethylolpropane acrylate and 0.5 kg of glycidyl methacrylate into a reaction kettle, and stirring under vacuum for 30 min at a vacuum degree of -0.8 MPa to obtain a mixture I;
[0088] S2. Add 2.8 kg of silicon dioxide as an insulating filler, 0.4 kg of vinyl triethoxysilane as a dispersant, 0.5 kg of 2-hydroxy-2-methylpropiophenone as an initiator and an antioxidant consisting of 0.05 kg of antioxidant 1010 and 0.05 kg of antioxidant 1076 to the mixture I, stir for 1 hour under a vacuum condition with a vacuum degree of -0.8 MPa, and then keep warm at a temperature of 35°C for 1 hour to obtain a UV insulating protective adhesive.
[0089] Example 2-3
[0090] The difference between Example 2-3 and Example 1 is that the amount of raw materials used and the preparation conditions are different, see Table 2 below for details.
[0091] Table 2 Raw material dosage and preparation conditions of Examples 1-3
[0092]
[0093]
[0094]
[0095] Embodiment 4-11
[0096] The difference between Example 4-11 and Example 3 is that the sources of fluorosilicone-modified acrylate are different, see Table 3 below for details.
[0097] Table 3 Sources of fluorosilicone modified acrylates of Examples 4-11
[0098] Example Source of Fluorosilicone Modified Acrylate Example 4 Preparation Example 1 Example 5 Preparation Example 2 Example 6 Preparation Example 3 Example 7 Preparation Comparative Example 1 Example 8 Preparation Comparative Example 2 Example 9 Preparation Comparative Example 3 Example 10 Preparation Comparative Example 4 Embodiment 11 Preparation Comparative Example 5
[0099] Example 12
[0100] The difference between Example 12 and Example 6 is that the types of dispersants are different. The dispersant in Example 12 is composed of castor oil-modified polyol and vinyl triethoxysilane. The amount of castor oil-modified polyol is 0.615 kg, and the amount of vinyl triethoxysilane is 0.185 kg. The rest is the same as Example 6.
[0101] Embodiment 13
[0102] The difference between Example 13 and Example 12 is that the amount of castor oil-modified polyol used is 0.5 kg, the amount of vinyl triethoxysilane used is 0.3 kg, and the rest is the same as Example 12.
[0103] Comparative Example
[0104] Comparative Example 1
[0105] The difference between Comparative Example 1 and Example 3 is that the fluorosilicone-modified acrylate is replaced by polyurethane acrylate in equal amounts, and the rest is the same as Example 3.
[0106] Comparative Example 2
[0107] The difference between Comparative Example 2 and Example 3 is that the dispersant is replaced by fluorosilicone-modified acrylate in equal amount, and the rest is the same as Example 3.
[0108] Performance test The following is a performance test of the UV insulation protective glue for new energy batteries prepared in Examples 1-13 and Comparative Examples 1-2:
[0109] (1) Adhesion stability test:
[0110] Apply UV insulation protective glue at 50g / m 2 The coating amount was applied to the stainless steel test plate, and then cured for 15 seconds under a LED UV lamp with a wavelength of 395nm. After being placed in a constant temperature and humidity chamber at a temperature of 85℃ and a humidity of 85%, it was placed for 42 days (1008 hours). The adhesion of the UV insulation protective glue was tested using the 100-grid test method, and the test results were tested and recorded.
[0111] (2) Insulation test
[0112] According to the test method of GB / T 1408.1-2016, use a voltage breakdown tester to test the dielectric strength (unit: KV / mm) of the UV insulation protective glue, and test and record the test results.
[0113] (3) Impact resistance test
[0114] According to the test method in GB / T 1732-2020, the impact strength of UV insulation protective adhesive is tested. The results are expressed as the maximum height (unit: cm) at which no cracks, wrinkles or peeling are observed in three parallel tests. The test results are tested and recorded;
[0115] (4) Salt spray resistance test
[0116] Apply UV insulation protective glue at 50g / m 2 The coating amount is applied to the stainless steel test plate and tested using standard neutral salt spray at a temperature of 35°C. When corrosion or discoloration occurs on the surface of the UV insulation protective adhesive, the test time (unit: h) is recorded.
[0117] The following are the test data of adhesion stability, insulation and impact resistance of the UV insulating protective glue for new energy batteries prepared in Examples 1-13 and Comparative Examples 1-2, see Table 4 below for details.
[0118] Table 4 Adhesion stability, insulation and impact resistance test data of Examples 1-13 and Comparative Examples 1-2
[0119]
[0120]
[0121] In combination with Examples 1-3 and Examples 4-11, Comparative Example 1 and Table 4, it can be seen that the fluorosilicone modified acrylate prepared by the present application is compounded with polyurethane acrylate to obtain a UV insulating protective adhesive with good adhesion stability, insulation and impact resistance. The adhesion can reach 5B after 1008h of the double 85 test, and the impact test height is increased from 30cm to 45cm. The salt spray corrosion resistance can reach 487h, and it is not easy to separate, fall off and puncture when applied to new energy batteries; in Examples 7-11, the fluorosilicone modified acrylate is not prepared by the preparation method of the present application, and the performance is reduced compared with Examples 4-6; and in Comparative Example 1, no fluorosilicone modified acrylate is added, and the performance of the obtained UV insulating protective adhesive is significantly reduced.
[0122] It can be seen from Examples 4-6 and Examples 12-13, Comparative Example 2 and Table 4 that the use of castor oil-modified polyols and vinyl triethoxysilane in a preferred ratio as a dispersant can further improve the adhesion stability, insulation and impact resistance of the prepared UV insulating protective adhesive. The impact strength in Example 13 is 50 cm, and the salt spray test can reach 500 h; in Comparative Example 1, the dispersant is replaced by fluorosilicone-modified acrylate in equal amounts, and the performance decreases, indicating that the dispersant of the present application can produce a good synergistic effect with fluorosilicone-modified acrylate, further improve the dispersion uniformity of the insulating filler and each component, and thus improve the adhesion stability, insulation and impact resistance of the prepared UV insulating protective adhesive, and at the same time, it can also improve the salt spray corrosion resistance of the UV insulating protective adhesive.
[0123] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A UV insulation protective glue for new energy batteries, characterized in that: Made from the following raw materials in parts by weight: Polyurethane acrylate 40-60 parts Fluorosilicone modified acrylate 10-20 parts Dilute monomer 25-35 parts Insulation filler 28-38 parts Photoinitiator 5-12 parts Dispersant 4-8 parts 1-3 parts of antioxidants; The fluorosilicone modified acrylate is prepared from the following raw materials in parts by weight: Methyl methacrylate 15-25 parts Polypropylene glycol diglycidyl ether 5-10 parts 4-6 parts of 4-hydroxybutyl acrylate glycidyl ether 3-8 parts of trifluoroethyl methacrylate 4-8 parts of vinyl trisbutyl ketoxime silane Solvent 20-30 parts Catalyst 0.1-0.3 parts Inhibitor 0.05-0.1 part; The fluorosilicone modified acrylate is prepared by the following steps: A1. Add methyl methacrylate, polypropylene glycol diglycidyl ether and 4-hydroxybutyl acrylate glycidyl ether into a reaction device, heat to 60-70° C., mix and stir for 20-40 minutes to obtain a mixture A; A2. Add trifluoroethyl methacrylate, vinyl tributylidene silane, a catalyst and a polymerization inhibitor to the mixture A, introduce nitrogen protection, raise the temperature to 85-95° C., react for 2-5 hours, and obtain fluorosilicone modified acrylate.
2. The UV insulating protective glue for new energy batteries according to claim 1, characterized in that: The diluent monomer is composed of a hydroxy acrylate monomer and a glycidyl ether acrylate monomer in a weight ratio of (2-3.5):(0.5-1.5).
3. The UV insulating protective glue for new energy batteries according to claim 1, characterized in that: The dispersant is composed of castor oil-modified polyol and vinyl triethoxysilane in a weight ratio of 1:(0.3-0.6).
4. The UV insulating protective glue for new energy batteries according to claim 1, characterized in that: The insulating filler is any one or a combination of silicon dioxide, silicon powder, aluminum nitride, zinc oxide, and white carbon black.
5. The UV insulating protective glue for new energy batteries according to claim 1, characterized in that: The photoinitiator is any one or a combination of 2-hydroxy-2-methylpropiophenone, 1-hydroxycyclohexyl phenyl ketone, and ethyl 2,4,6-trimethylbenzoylphenylphosphonate.
6. The UV insulating protective glue for new energy batteries according to claim 1, characterized in that: The antioxidant is a combination of at least two of the antioxidant 1010 , the antioxidant 1076 , the antioxidant 168 , and the antioxidant 626 .
7. A method for preparing a UV insulating protective adhesive for new energy batteries according to any one of claims 1 to 6, characterized in that: The following steps are involved: S1, adding polyurethane acrylate, fluorine silicon modified acrylate and diluent monomer into a reaction device, and performing vacuum stirring to obtain a mixture I; S2. Add insulating filler, initiator, dispersant and antioxidant to mixture I, stir evenly in vacuum, and keep warm to obtain UV insulating protective adhesive.
8. The method for preparing a UV insulating protective adhesive for new energy batteries according to claim 7, characterized in that: In the steps S1-S2, the vacuum degree of vacuum stirring is -0.8 MPa--1.0 MPa; the insulation time in the step S2 is 1-2 h, and the insulation temperature is 35-45°C.
Citation Information
Patent Citations
UV-LED curing coating and preparation method thereof
CN112126262A
Protective film applied to new energy battery shell and preparation method of protective film
CN117050668A
Fluorosilicone modified acrylate resin, stain-resistant coating and preparation method of fluorosilicone modified acrylate resin and stain-resistant coating
CN117534797A